ChemInform Abstract: Bisoxazoline‐Catalyzed Asymmetric Nucleophilic Addition of Diethyl Zinc to Fluorinated Alkyl Ketones: Enantiofacial Control by Changing the Bisoxazoline Substituent. Issue 24 (June 2015) - Sasaki, Shigeru; Yamauchi, Takayasu; Kanai, Masatomi; Ishii, Akihiro; Higashiyama, Kimio
Abstract: Optimum reaction conditions (structure of catalyst, solvent) are studied for the bisoxazoline‐catalyzed asymmetric nucleophilic addition of diethyl zinc to fluorinated alkyl ketones.